Potential diversification benefits across global Islamic equity markets - Abd. Majid, M. Shabri; Kassim, Salina (The Statistical, Economic and Social Research and Training Centre for Islamic Countries (SESRIC), 2010)
In view of the increasing interests on the Islamic stock markets as a potential avenue for portfolio diversification, this study is indeed timely to assess the degree of integration among five major Islamic stock markets, namely Malaysia, Indonesia, Japan, the UK and the US. It also attempts to empirically explore the nature of the long-run equilibrium relationship among the major Islamic stock indexes and to examine the dynamic causal linkages among them. Based on weekly closing stock indexes of the selected stock markets from 1 January 1999 to 31 August 2006, this study relies on a two-step estimation using the Auto- Regressive Distributed Lag (ARDL) and the Vector Error Correction Model (VECM) based on the Generalized Method of Moments (GMM). The study finds that investors who are interested to diversify their portfolio can gain benefits by diversifying in the Islamic stock markets across economic grouping such as that in the developed and developing countries. However, limited benefits are available if investors only diversify their investments within the same economic groupings.